The incidence of peripheral neuropathy in HIV-Positive individuals on highly active antiretroviral therapy (HAART) - Pillay, Prinisha (My University, 2014)
Peripheral sensory neuropathy is a common neurological complication of antiretroviral therapy, typically occurring within 6-months of starting Highly Active Antiretroviral Therapy (HAART) which includes stavudine. Therefore, the primary aim of the study was to determine the 6-month incidence of ATN in patients free of neuropathy and beginning stavudine-based HAART for the first time. Also, we examined whether initiating stavudine-based HAART altered the symptoms of patients who had a pre-existing, virus-mediated distal symmetrical polyneuropathy (HIV-DSP). Seventy-five HIV-positive patients were screened for neuropathy, at the Chris-Hani Baragwanath Hospital, using the AIDS Clinical Trials Group neuropathy screening tool. The bilateral presence of atleast one sign (decreased vibration sense in the great toe or absent ankle reflex) and one symptom (pain, paraesthesia or numbness) in the feet was indicative of neuropathy. On recruitment, 52 patients presented without neuropathy and 13 patients presented with HIV-DSP. After 3- months of follow-up (n=46), 23% (10/46) of patients had developed peripheral neuropathy, and by 6-months (n=44), 41% (18/44) of patients had developed neuropathy. Greater disease severity was the only risk factor significantly associated with the development of neuropathy. Eleven (61%) of the 18 patients that developed neuropathy, developed painful symptomatic neuropathy, and only 6 (55%) of these patients were receiving treatment for symptom relief. In patients with HIV-DSP, numbness was the most common symptom reported at baseline and was the only symptom to reduce in frequency across the 6-months. In conclusion, we found that the development of neuropathy is common in the first 6-months of patients initiating stavudine-based HAART.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of MSc (Med) Johannesburg, 2011
Keywords: Antiretroviral Therapy, Highly Active; HIV--complications; Peripheral Nervous System Diseases